2011
DOI: 10.1002/jbmr.517
|View full text |Cite
|
Sign up to set email alerts
|

Subtrochanteric/femoral shaft Versus hip fractures: Incidences and identification of risk factors

Abstract: Subtrochanteric and femoral shaft (ST/FS) fractures are now considered to be fragility fractures in osteoporotic patients. Although rare, there is growing evidence of the burden that they constitute. Little is known about the change over time in incidence of ST/FS fractures. We assessed the incidence of ST/FS fractures and the associated risk factors from 2002 to 2009 compared with those of hip fractures. Data were obtained from the French National Database, which includes all hospital discharge codes from acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 33 publications
1
7
1
Order By: Relevance
“…This ratio dropped down to 7.35%, when determined by radiological analysis and after excluding pathological, traumatic and per prosthetic fractures, fragility ST/FS fractures only represented 2.25% of all femoral fractures in our study. This result is much lower than previously reported [1,3,9,10,17,21], suggesting a potential bias in the interpretation of the study results only based on registered data related to a high rate of miscoding specific to this fracture location. Misclassification has been previously reported in literature.…”
Section: Discussioncontrasting
confidence: 83%
“…This ratio dropped down to 7.35%, when determined by radiological analysis and after excluding pathological, traumatic and per prosthetic fractures, fragility ST/FS fractures only represented 2.25% of all femoral fractures in our study. This result is much lower than previously reported [1,3,9,10,17,21], suggesting a potential bias in the interpretation of the study results only based on registered data related to a high rate of miscoding specific to this fracture location. Misclassification has been previously reported in literature.…”
Section: Discussioncontrasting
confidence: 83%
“…Over the 5‐year study period, the number of prescriptions of BP increased significantly. In summary, most studies, although not all, have found the incidence of ST/FS fractures has increased and that the age‐adjusted rate of these fractures in women is between 10 and 35 per 100,000.…”
Section: Update On Epidemiology and Risk Factorsmentioning
confidence: 93%
“…This rise in incidence mainly occurred in women over age 60 years and was accounted for by minimal to moderate trauma fractures. An analysis of the French National Database found that age‐adjusted FN/IT fracture incidence in women decreased significantly between 2002 and 2009, but incidence of ST/FS increased significantly . Lee and colleagues used national claims data to identify hip and femur fractures in South Korea, based on ICD‐10 codes.…”
Section: Update On Epidemiology and Risk Factorsmentioning
confidence: 99%
“…Atypical femoral fractures have been an increasing concern in the treatment of osteoporosis, especially with bisphospho- nates (13)(14)(15)(16)(17). Our objectives were to evaluate the clinical results with incomplete atypical femoral fractures and to determine factors associated with the requirement for fixation in these conditions.…”
Section: Discussionmentioning
confidence: 98%